2006
DOI: 10.1136/jme.2005.014456
|View full text |Cite
|
Sign up to set email alerts
|

Non-reporting and inconsistent reporting of race and ethnicity in articles that claim associations among genotype, outcome, and race or ethnicity

Abstract: Background: The use of race as a category in medical research is the focus of an intense debate, complicated by the inconsistency of presumed independent variables, race and ethnicity, on which analysis depends. Interpretation is made difficult by inconsistent methods for determining the race or ethnicity of a participant. The failure to specify how race or ethnicity was determined is common in the published literature. Hypothesis: Criteria by which they assign a research participant to racial or ethnic catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 43 publications
6
39
0
Order By: Relevance
“…Our finding that none of the asthma clinical trials explained how they assigned race/ethnicity classes to their patients (e.g., whether self-reported or researcher-assigned) is broadly consistent with results of a study by Shanawani, Dame, Schwartz, and Cook-Deegan (2006) which showed that the majority of medical research articles claiming associations among genotype, outcome and race/ethnicity did not explain their methods for assigning race or ethnicity.…”
Section: Discussionsupporting
confidence: 78%
“…Our finding that none of the asthma clinical trials explained how they assigned race/ethnicity classes to their patients (e.g., whether self-reported or researcher-assigned) is broadly consistent with results of a study by Shanawani, Dame, Schwartz, and Cook-Deegan (2006) which showed that the majority of medical research articles claiming associations among genotype, outcome and race/ethnicity did not explain their methods for assigning race or ethnicity.…”
Section: Discussionsupporting
confidence: 78%
“…Despite widespread knowledge of the confounding factors of language background, SES, and racial/ ethnic background [8,16,26,44], however, many language focused studies still do not consider SES in their research design or they exclude participants whose primary language is not English. The deficiencies in UP representation in treatment studies have important implications for clinicians who serve a population increasing in both ASD diagnoses and diversity, and in the pursuit of evidence-based practice for all, recommendations have been made to recruit more inclusive samples.…”
Section: Discussionmentioning
confidence: 99%
“…Because it is largely unknown whether specific UP types moderate ASD treatment [8,44] or particular UP characteristics are correlated with other factors, such as treatment setting or target, an analysis beyond simple frequency of UP inclusion is essential.…”
Section: Up Trends By Treatment Targetmentioning
confidence: 99%
“…Most studies do not report how race information is obtained [28], e.g., self-identified or clinician determined, let alone standardize the process. The definition of race is also time-and geography-dependent [16].…”
Section: Race In Medicinementioning
confidence: 99%
“…Some believe race should not be used in medicine and research [23]. They believe avoiding classifying people by race will help promote recognition of the heterogeneity within groups [28] and continuing its use will derail true genetic research [19]. Focusing on racial health disparities also directs resources away from the true social, environmental, and other drivers of unequal disease distribution [29].…”
Section: Race In Medicinementioning
confidence: 99%